A facile one-step approach for the fabrication of polypyrrole nanowire/carbon fiber hybrid electrodes for flexible high performance solid-state supercapacitors. (2nd October 2017) - Huang, Sanqing; Han, Yichuan; Lyu, Siwei; Lin, Wenzhen; Chen, Peishan; Fang, Shaoli
Abstract: Wearable electronics are in high demand, requiring that all the components are flexible. Here we report a facile approach for the fabrication of flexible polypyrrole nanowire (NPPy)/carbon fiber (CF) hybrid electrodes with high electrochemical activity using a low-cost, one-step electrodeposition method. The structure of the NPPy/CF electrodes can be easily controlled by the applied electrical potential and electrodeposition time. Our NPPy/CF-based electrodes showed high flexibility, conductivity, and stability, making them ideal for flexible all-solid-state fiber supercapacitors. The resulting NPPy/CF-based supercapacitors provided a high specific capacitance of 148.4 F g −1 at 0.128 A g −1, which is much higher than for supercapacitors based on polypyrrole film/CF (38.3 F g −1 ) and pure CF (0.6 F g −1 ) under the same conditions. The NPPy/CF-based supercapacitors also showed high bending and cycling stability, retaining 84% of the initial capacitance after 500 bending cycles, and 91% of the initial capacitance after 5000 charge/discharge cycles.